Akkermansia muciniphila promotes type H vessel formation and bone fracture healing by reducing gut permeability and inflammation - Jiang-Hua Liu; Tao Yue; Zhong-Wei Luo; Jia Cao; Zi-Qi Yan; Ling Jin; Teng-Fei Wan; Ci-Jun Shuai; Zheng-Guang Wang; Yong Zhou; Ran Xu; Hui Xie (The Company of Biologists, 2020)
Improving revascularization is one of the major measures in fracture treatment. Moderate local inflammation triggers angiogenesis, whereas systemic inflammation hampers angiogenesis. Previous studies showed that Akkermansia muciniphila, a gut probiotic, ameliorates systemic inflammation by tightening the intestinal barrier. In this study, fractured mice intragastrically administrated with A. muciniphila were found to display better fracture healing than mice treated with vehicle. Notably, more preosteclasts positive for platelet-derived growth factor-BB (PDGF-BB) were induced by A. muciniphila at 2 weeks post fracture, coinciding with increased formation of type H vessels, a specific vessel subtype that couples angiogenesis and osteogenesis, and can be stimulated by PDGF-BB. Moreover, A. muciniphila treatment significantly reduced gut permeability and inflammation at the early stage. Dextran sulfate sodium (DSS) was used to disrupt the gut barrier to determine its role in fracture healing and whether A. muciniphila still can stimulate bone fracture healing. As expected, A. muciniphila evidently improved gut barrier, reduced inflammation and restored the impaired bone healing and angiogenesis in DSS-treated mice. Our results suggest that A. muciniphila reduces intestinal permeability and alleviates inflammation, which probably induces more PDGF-BB+ preosteoclasts and type H vessel formation in callus, thereby promoting fracture healing. This study provides the evidence for the involvement of type H vessels in fracture healing and suggests the potential of A. muciniphila as a promising strategy for bone healing. This article has an associated First Person interview with the first author of the paper.